(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to diagnose and analyze the gap between the actual reality and the application of the eighth requirement (operation) in the National Insurance Company in accordance with the international standard specification for the quality management system (ISO 9001:2015), which is related to the planning, implementation and control of operations, which would raise the level of performance of employees and be reflected in the provision of An appropriate service for the faithful, as the reality of the condition of the requirement was studied by identifying the strengths and weaknesses of the system to diagnose the gap and find ways to address it. A workshop was held with company officials, through which questions were raised that were included in the checklist. The necessary data were collected to measure the extent of application and documentation based on percentages and weighted arithmetic mean. The research reached a number of results, the most prominent of which was the existence of a gap in the operational requirement that Its percentage (43%), meaning that the level of application and documentation of this requirement reached (57%), and this does not achieve the required degree of conformity with the requirement in the international standard, so it requires the researched company to address the gaps through improvement. and a review of the system to bridge those gaps.